giúp em vs ạ em cần gấp lắm

Question

giúp em vs ạ em cần gấp lắm
giup-em-vs-a-em-can-gap-lam

in progress 0
Ladonna 9 months 2020-10-28T18:16:26+00:00 1 Answers 57 views 0

Answers ( )

    0
    2020-10-28T18:17:38+00:00

    Đáp án:

    d. \(Max = \dfrac{2}{3}\)

    Giải thích các bước giải:

    \(\begin{array}{l}
    A = \dfrac{{15\sqrt x  – 11 – \left( {3\sqrt x  – 2} \right)\left( {\sqrt x  + 3} \right) – \left( {2\sqrt x  + 3} \right)\left( {\sqrt x  – 1} \right)}}{{\left( {\sqrt x  + 3} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \dfrac{{15\sqrt x  – 11 – 3x – 7\sqrt x  + 6 – 2x – \sqrt x  + 3}}{{\left( {\sqrt x  + 3} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \dfrac{{ – 5x + 7\sqrt x  – 2}}{{\left( {\sqrt x  + 3} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \dfrac{{\left( {2 – 5\sqrt x } \right)\left( {\sqrt x  – 1} \right)}}{{\left( {\sqrt x  + 3} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \dfrac{{2 – 5\sqrt x }}{{\sqrt x  + 3}}\\
    b.A = \dfrac{1}{2}\\
     \to \dfrac{{2 – 5\sqrt x }}{{\sqrt x  + 3}} = \dfrac{1}{2}\\
     \to 4 – 10\sqrt x  = \sqrt x  + 3\\
     \to 11\sqrt x  = 1\\
     \to \sqrt x  = \dfrac{1}{{11}}\\
     \to x = \dfrac{1}{{121}}\\
    c.Thay:x = 3 – 2\sqrt 2 \\
     = 2 – 2\sqrt 2 .1 + 1 = {\left( {\sqrt 2  – 1} \right)^2}\\
     \to A = \dfrac{{2 – 5\sqrt {{{\left( {\sqrt 2  – 1} \right)}^2}} }}{{\sqrt {{{\left( {\sqrt 2  – 1} \right)}^2}}  + 3}}\\
     = \dfrac{{2 – 5\left( {\sqrt 2  – 1} \right)}}{{\sqrt 2  – 1 + 3}} = \dfrac{{7 – 5\sqrt 2 }}{{\sqrt 2  – 2}}\\
    d.A = \dfrac{{2 – 5\sqrt x }}{{\sqrt x  + 3}} = \dfrac{{ – 5\left( {\sqrt x  + 3} \right) + 17}}{{\sqrt x  + 3}}\\
     =  – 5 + \dfrac{{17}}{{\sqrt x  + 3}}\\
    Do:\sqrt x  \ge 0 \to \sqrt x  + 3 \ge 3\\
     \to \dfrac{{17}}{{\sqrt x  + 3}} \le \dfrac{{17}}{3}\\
     \to  – 5 + \dfrac{{17}}{{\sqrt x  + 3}} \le  – 5 + \dfrac{{17}}{3}\\
     \to  – 5 + \dfrac{{17}}{{\sqrt x  + 3}} \le \dfrac{2}{3}\\
     \to Max = \dfrac{2}{3}\\
     \Leftrightarrow x = 0
    \end{array}\)

     

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )